2013
DOI: 10.1039/c2tc00020b
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, phase evolution and ferroelectric properties of sol–gel-synthesized Ba(Ti0.8Zr0.2)O3–x(Ba0.7Ca0.3)TiO3thin films

Abstract: A lead-free piezoelectric material with ultra-high properties, Ba(Ti0.8Zr0.2)O3-x(Ba0.7Ca0.3)TiO3(BZTxBCT) nanocrystals was synthesized via a sol-gel method, and the corresponding thin films were also deposited on Pt/Ti/SiO2/Si substrates by a spin-coating approach. The BZT-xBCT thin film exhibited a high remnant polarization of 22.15 mC cm2 with a large coercive field of 68.06 kV cm1. The resultant gel is calcined at various elevated temperatures and studied with FTIR/XRD/Raman/DSC-TGA/AFM/SEM techniques for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 45 publications
7
61
1
Order By: Relevance
“…Broadening of (0 0 2) peaks with compositions x ≥ 0.5 indicates the splitting of the peak into (0 0 2) and (2 0 0) peaks, which is a signature of tetragonal phase. A phase transformation from rhombohedral to tetragonal phase thus can be inferred starting from x = 0.5 [12]. The in-plane growth relationship between the film and the substrate was also confirmed by the XRD off-axis scan of the (2 0 2) peak.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Broadening of (0 0 2) peaks with compositions x ≥ 0.5 indicates the splitting of the peak into (0 0 2) and (2 0 0) peaks, which is a signature of tetragonal phase. A phase transformation from rhombohedral to tetragonal phase thus can be inferred starting from x = 0.5 [12]. The in-plane growth relationship between the film and the substrate was also confirmed by the XRD off-axis scan of the (2 0 2) peak.…”
Section: Resultsmentioning
confidence: 85%
“…These factors are processing and technique dependent and may lead to diverse properties of the thin films. Kang et al [11] found the best ferroelectric characteristic lied at x = 0.45 with a remnant polarization P r of 15.8 C/cm 2 in CSD-produced BZT-xBCT thin films while P r reached 22.15 C/cm 2 when x = 0.5 with spin-coating approach [12]. Lin et al [13] employed sol-gel method and the largest tunability up to 65% at 400 kV/cm at 100 kHz was achieved in BZT-0.55BCT film.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The remnant polarization (P r ) values and the coercive field (V c ) were 10 lC/cm 2 and 5 V, respectively, which were slightly lower than our previous results. 24 The hardness and elastic modulus of the BZT-0.5BCT film were measured using a Micro Materials NanoTest with a Berkovich diamond indenter at different temperatures, room temperature (RT), and 60, 95, and 120 C. Nanoindentation has been proven to be a powerful technique for characterization of the mechanical response of nanoscale materials. The surface and substrate effects are negligible if the nanoindentation tests are performed at certain penetration depths less than one tenth of the film thickness.…”
mentioning
confidence: 99%
“…The BZT-0.5BCT film was prepared via a sol-gel method on Pt(111)/Ti/SiO 2 /Si(100) substrate by annealing at 850 C according to a previously described procedure, 24 and the film thickness was $1 lm. The phase structure of the BZT-xBCT thin film was characterized by using XRD in a Bruker AXS D8 DISCOVER with Cu K a radiation (k ¼ 1.5405 Å ).…”
mentioning
confidence: 99%